Phytochemical and toxicological evaluation of aqueous leaf extract of Premna integrifolia L. in male balb/c mice - Suman; Pratibha Gaurav; Rajesh Saini; Kavindra Nath Tiwari; Gautam Geeta Jiwatram (Elsevier, 2025)
Background: Phytoconstituents present in plants provide a natural and comprehensive method for combating oxidative stress and various ailments. Safety evaluation of these herbal medications is necessary, so acute and sub-acute toxicity of plant leaf extract Premna integrifolia has been performed to standardize its dose regarding its therapeutic application in male fertility. Purpose: Toxicological evaluation Aqueous leaf extract of Premna integrifolia (ALEPI), a known herbal medicine, for its utilization in male fertility enhancement use. Study design and methods: To assess the safety and pharmacological potential of the ALEPI, acute and subacute toxicity studies were carried out in compliance with the OECD guidelines No. 425 and 407, respectively. Identification of pharmacologically active compounds in ALEPI was performed using UHPLC-HRMS analysis. In vitro, estimation of Polyphenol Content, Total Flavonoid Content, saponins and Antioxidant Properties of ALEPI was performed. The oral acute toxicity of the ALEPI was conducted using male mice. The study involved administering single doses of ALEPI at 300, 2000, and 5000 mg/kg b.wt., followed by a fourteen-day observation period to monitor any signs of toxicity or adverse effects. In the oral subacute toxicity study, mice received daily oral gavage of the ALEPI at doses of 400, 800, and 1000 mg/kg b.wt. for twenty-eight days. The parameters studied included total reactive oxygen species (ROS) production, apoptosis, cell viability percentage, and cellular morphology. Results: The UHPLC-HRMS analysis of the ALEPI reveals the presence of various bioactive compounds with significant antioxidant, anti-inflammatory, and anticancer properties. The acute and subacute toxicity studies of the ALEPI provided a comprehensive evaluation of its safety profile. Both studies demonstrated no mortality and only minor alterations in relative organ weights, hematology, and serum biochemistry, suggesting a low toxicity profile. Additionally, the normal histoarchitecture of vital organs indicates the absence of significant morphological changes. Significant reduction in total ROS, necrosis percentage, and apoptosis in testicular tissue compared to the control group highlights the antioxidant properties of the extract. Conclusion: Based on the findings from both the acute and subacute toxicity studies, it is evident that the ALEPI does not actuate adverse effects of toxicological significance at the tested doses and hence can be used at appropriate concentrations in therapeutic application.